The thesis writing journeys of bachelor's and master's students : a transnational European perspective - Petrić, Bojana; Castelló, Montserrat, 1960- (Multilingual Matters, 2025)
"This book explores the student experience of thesis writing through an interdisciplinary perspective drawing on theories of learning, emotions, and genre and narrative/discursive analysis. As a result of this approach, the thesis is reconceptualised as a multilayered experience from the point of view of student writers"-- Provided by publisher.
Keywords: Academic writing -- Europe.; Dissertations, Academic -- Europe.; College students -- Europe.; Thèses et écrits académiques -- Europe.; Étudiants -- Europe.; EDUCATION / Adult & Continuing Education